Synergies and trade-offs among key ecosystem services in Maze National Park and its environs, southwestern Ethiopia - Mestewat Simeon; Desalegn Wana (Global Ecology and Conservation)
The aim of this study is to assess synergies and trade-offs between ecosystem services in Maze National Park and its environs in southwestern Ethiopia. We employed land use and land cover data along with ecosystem services values from previous studies and performed a landscape diversity analysis to examine correlations with ecosystem services dynamics. The spatiotemporal trade-offs/synergy relationships were analyzed using ecosystem service values from the years 1985, 1995, 2005, 2015, and 2020, employing the Spearman correlation coefficient and the Local Moran’s I autocorrelation model. Additionally, we collected socioeconomic data to get insight into the local people’s perceptions of the interactions between ecosystem services. The landscape metrics results revealed a rise in the number of patches, patch density, and edge density, indicating landscape fragmentation. From 1985–2020, food production service exhibited a moderate negative correlation with water supply (rs = −0.6), raw material (rs = −0.5), and climate regulation (rs = −0.5), indicating a moderate trade-off relationship. Conversely, a very strong and significant positive correlation (rs = 1), indicating a strong synergistic relationship, was observed between raw material and climate regulation, water supply and climate regulation (rs = 0.9), and raw material and water supply services (rs = 0.9). Spatially, the relationships among ecosystem services were predominantly synergistic, though a higher proportion of trade-offs was observed between food production and other services. The Chi-Square test results indicated that local community perceptions of the interactions between ecosystem services vary depending on their distance from the park. Therefore, understanding the relationships between ecosystem services is crucial for developing effective ecosystem protection strategies and addressing the effects of anthropogenic disturbances in protected areas and beyond. Finally, we recommend future studies to incorporate additional provisioning, regulating, and cultural services to fully represent the region's ecosystem services status in trade-offs and synergy analyses.